Development of the genetic code: insights from a fungal codon reassignment - Moura, Gabriela R. (2010)
The high conservation of the genetic code and its fundamental role in genome decoding suggest that its evolution is highly restricted or even frozen. However, various prokaryotic and eukaryotic genetic code alterations, several alternative tRNA-dependent amino acid biosynthesis pathways, regulation of tRNA decoding by diverse nucleoside modifications and recent in vivo incorporation of non-natural amino acids into prokaryotic and eukaryotic proteins, show that the code evolves and is surprisingly flexible. The cellular mechanisms and the proteome buffering capacity that support such evolutionary processes remain unclear. Here we explore the hypothesis that codon misreading and reassignment played fundamental roles in the development of the genetic code and we show how a fungal codon reassignment is enlightening its evolution.